Chapter Speaker and quote reduced parenthetical clauses - Griffiths , James (De Gruyter, 2015)
In this paper, I present a syntactico-pragmatic delimitation and subsequent analysis of reduced parenthetical clause constructions that is based upon Schneider's (2007a) superordinate and binary division between reduced parenthetical clauses that modify quotes, and those that modify utterances of any other illocutionary type. I argue that the parentheticals in question can receive a unified analysis, and that, by splitting them asunder according to the type of host they modify, the vast majority of the seemingly disparate properties they display can be readily accounted for.